Creative Economy Promotion Model As Culinary Tourism In Kranggan Lumpia Leather Center, Semarang City - Amelia Tri Nursifa; Nina Mistriani; Ayu Puspita Rini; Flores Harliesyahputra Laia; Haidar Hafiiz Azzam; Herni Susanti Ndruru; Melvannisa Ayu Dara Ninggar; Yasmin Carolina Gea (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Creative activities are related to the food and beverage business which is popular with the public and adds value to the creative products of culinary industry players. The aim of the research is to analyze and develop the creative economy of the culinary tourism sector in Kranggan Village, Semarang City. This research uses a qualitative descriptive approach with survey and interview methods. The promotional model developed integrates the following elements: Promoting local culinary delights, collaborating with culinary industry players, and using a word of mouth promotion model. The research results show that this promotional model has succeeded in increasing visits to local culinary destinations in encouraging culinary business growth. The promotion model has become a tradition and cultural identity for the culinary industry around Kranggan Village, Semarang City. So that the Lumpia Skin Center is known to the public and culinary businesses in Semarang City. This has an impact on the economy of the surrounding community, as well as the creation of jobs in the creative economy sector.